At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Let's start with the initial function [tex]\( f(x) = x^5 \)[/tex] and apply the given transformations step by step.
1. Shift left by 1 unit:
When we shift a function [tex]\( f(x) \)[/tex] to the left by 1 unit, we replace [tex]\( x \)[/tex] with [tex]\( x + 1 \)[/tex]. Thus,
[tex]\[ f(x) = x^5 \quad \Rightarrow \quad f(x+1) = (x+1)^5 \][/tex]
2. Reflect over the [tex]\( y \)[/tex]-axis:
Reflecting a function over the [tex]\( y \)[/tex]-axis involves replacing [tex]\( x \)[/tex] with [tex]\( -x \)[/tex]. So, we apply this to the shifted function:
[tex]\[ f(x+1) = (x+1)^5 \quad \Rightarrow \quad f(-x+1) = (-x+1)^5 \][/tex]
3. Vertically compress by [tex]\(\frac{1}{3}\)[/tex]:
To vertically compress a function by [tex]\(\frac{1}{3}\)[/tex], we multiply the function by [tex]\(\frac{1}{3}\)[/tex]. Thus,
[tex]\[ f(-x+1) = (-x+1)^5 \quad \Rightarrow \quad \frac{1}{3}(-x+1)^5 \][/tex]
So, after applying all the transformations to [tex]\( f(x) = x^5 \)[/tex], the resulting function is
[tex]\[ \boxed{\frac{1}{3}(-x+1)^5} \][/tex]
Comparing this result to the options provided:
A. [tex]\( f(x) = \left(-\frac{1}{3} x + 1\right)^5 \)[/tex]
B. [tex]\( f(x) = \frac{1}{3}(-x+1)^5 \)[/tex]
C. [tex]\( f(x) = \frac{1}{3}(-x)^5 + 1 \)[/tex]
D. [tex]\( f(x) = \frac{1}{3}(-x-1)^5 \)[/tex]
The correct answer is:
[tex]\[ \boxed{B} \][/tex]
1. Shift left by 1 unit:
When we shift a function [tex]\( f(x) \)[/tex] to the left by 1 unit, we replace [tex]\( x \)[/tex] with [tex]\( x + 1 \)[/tex]. Thus,
[tex]\[ f(x) = x^5 \quad \Rightarrow \quad f(x+1) = (x+1)^5 \][/tex]
2. Reflect over the [tex]\( y \)[/tex]-axis:
Reflecting a function over the [tex]\( y \)[/tex]-axis involves replacing [tex]\( x \)[/tex] with [tex]\( -x \)[/tex]. So, we apply this to the shifted function:
[tex]\[ f(x+1) = (x+1)^5 \quad \Rightarrow \quad f(-x+1) = (-x+1)^5 \][/tex]
3. Vertically compress by [tex]\(\frac{1}{3}\)[/tex]:
To vertically compress a function by [tex]\(\frac{1}{3}\)[/tex], we multiply the function by [tex]\(\frac{1}{3}\)[/tex]. Thus,
[tex]\[ f(-x+1) = (-x+1)^5 \quad \Rightarrow \quad \frac{1}{3}(-x+1)^5 \][/tex]
So, after applying all the transformations to [tex]\( f(x) = x^5 \)[/tex], the resulting function is
[tex]\[ \boxed{\frac{1}{3}(-x+1)^5} \][/tex]
Comparing this result to the options provided:
A. [tex]\( f(x) = \left(-\frac{1}{3} x + 1\right)^5 \)[/tex]
B. [tex]\( f(x) = \frac{1}{3}(-x+1)^5 \)[/tex]
C. [tex]\( f(x) = \frac{1}{3}(-x)^5 + 1 \)[/tex]
D. [tex]\( f(x) = \frac{1}{3}(-x-1)^5 \)[/tex]
The correct answer is:
[tex]\[ \boxed{B} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.